Menopausal hormone therapy in certain diseases of therapeutic profile - I. V. Madyanov; T. S. Madyanova (Лечащий Врач, 2021)
The article presents modern approaches to the use of menopausal hormone therapy (MHT) in certain diseases of therapeutic profile. It is shown that, in rational choice of MHT, it can be successfully used almost in all diseases of therapeutic profile.